2021
DOI: 10.1177/15330338211045497
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Modulation Factor on Treatment Plan Quality and Irradiation Time in Hippocampus-Sparing Whole-Brain Radiotherapy Using Tomotherapy

Abstract: Objectives: Hippocampus-sparing whole-brain radiotherapy (HS-WBRT) using tomotherapy is known to provide a better dose distribution than volumetric-modulated arc therapy but requires an extended irradiation time. The present study aimed to investigate whether irradiation time can be shortened by reducing the modulation factor (MF) without losing the target dose distribution. Methods: Using six tilted computed tomography images in the head area, the planning target volume (PTV) and hippocampal doses, and the ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Miura et al 15 reported that the irradiation time was reduced by approximately 10% after applying tilt in tomotherapy. Ishibashi et al 16 reported a reduction in the irradiation time by 30% after reducing the modulation factor. Moreover, Shimizu et al reported that irradiation time can be shortened to 6 min using a 2.5 cm jaw.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Miura et al 15 reported that the irradiation time was reduced by approximately 10% after applying tilt in tomotherapy. Ishibashi et al 16 reported a reduction in the irradiation time by 30% after reducing the modulation factor. Moreover, Shimizu et al reported that irradiation time can be shortened to 6 min using a 2.5 cm jaw.…”
Section: Discussionmentioning
confidence: 99%
“…As in this study, 66–75 rotations, with each rotation lasting for 21–23 s, were used for HS-WBRT; at least 11.8 s per revolution is required for tomotherapy. 16 , 18 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, when the pitch was large (≥0.25), lowering the MF until the gantry speed was maximized reduced both treatment time and plan quality [8]. Furthermore, Ishibashi et al reported that MF reduction from 3.0 to 1.8 in hippocampus-sparing whole-brain irradiation resulted in almost no deterioration in plan quality and a shorter irradiation time [9]. The irradiation time at an MF of 1.8 was approximately 60% of that at an MF of 3.0, and the irradiation time decreased linearly during this period.…”
Section: Discussionmentioning
confidence: 99%